Influence of urbanization on regional habitat quality:a case study of Changchun City. (November 2019) - Bai, Limin; Xiu, Chunliang; Feng, Xinghua; Liu, Daqian
Abstract: Habitat is one of the important research contents of regional ecological security. Based on land use data, this paper analyzes the spatio-temporal characteristics of Changchun's landscape pattern, habitat quality and its sample zone on the basis of comprehensive utilization of spatial analysis and ecological model analysis, and further discusses the spatial heterogeneity of the impact of urbanization on habitat quality. The results show that first, there is a typical correlation between landscape pattern and topography. Urban expansion promotes patch density(PD), edge density(ED) and Shannon's diversity index (SHDI) of built-up areas, but lowers the aggregation index(AI) level. Second, the overall degradation of the habitat quality is obvious. The significant degradation area is mainly located in the urban expansion areas, mountainous and hilly areas, and areas along the traffic. The ecological protection area of Dahei mountains has a high level of habitat quality. The fluctuation frequency and amplitude of habitat in the four sample zones are affected by both topography and human activities. Plain areas and the intensification of human activities will lead to the gradual degradation of habitat quality. Relatively complete high-quality habitat areas are mostly distributed in mountainous areas or areas with weak human activity intensity. Third, the natural environment determines the overall distribution pattern of habitat, while human activities play a leading role in habitat change. The degree of impact of urbanization speed and breadth on habitat is characterized by significant heterogeneity. The impact of settlements on habitat quality is affected by both scale and landscape pattern. Under the background of rapid urbanization, problems such as the degradation of habitat quality, the habitat integrity of ecological protection area is under many threats appear gradually in Changchun city. Therefore, this article puts forward to prevent arable land expansion and deforestation in the forest area of the Dahei mountains, implement "returning farmland to forest and grass", improve land use efficiency of built-up areas, set urban growth boundary, delimit the red line of farmland protection, adopt a policy of "rotation and rest" in economic forest and grass area, and promote the recover of regional habitat quality by ecological means. Highlights: Urbanization and ecological environmental protection are the important aspects for planning. Spatial heterogeneity of habitat quality was quantified from the double scale of grid and sample. Quantitativily analysis the response relationship between urbanization and habitat quality. The habitat protection and promotion strategies under the background of urbanization is proposed.